Prototyping of a Smart, Secure and Multipurpose Flash Pen Drive - Benjamin Kommey; Prosper Ocloo Nulako Kwaku; Gabriel Ib-Nemwin Peguu; Daniel Opoku; Kwame Agyeman Prempeh Agyekum (Universitas Andalas, 2026)
Unlike traditional pen-drives, the proposed device incorporates biometric authentication, wireless file access, local encryption, and real-time display feedback within a compact embedded system. The prototype is based on a dual microcontroller architecture, using the STM16F103C8T6 as the master controller for system logic and security, and the ESP16-WROOM for wireless connectivity and mobile interaction. Key features of the device include fingerprint-based user access control, AES encryption for secure file storage, battery-powered offline operation, and a display interface to inform users of transfer progress, battery life, and wireless status. The system also includes a custom communication protocol between the two microcontrollers to ensure synchronized behavior between authentication and Wi-Fi access. Two physical models were envisioned and prototyped: one using buttons and a compact OLED display, and another with a touchscreen interface for advanced control. The report outlines the methodology, system architecture, component selection, PCB design, firmware logic, and testing strategy. While the prototype is still under development, the design has been validated through detailed simulation, testing of individual modules, and real-world power and thermal calculations. The project demonstrates the feasibility of building a modern, user-friendly USB drive that merges data security, IoT accessibility, and mobile independence.